A survey of augmented reality: making technologies acceptable in outdoor environments - Pascoal, R. (2018)
Augmented Reality (AR) is an increasingly prevalent subject with various areas of application. This work explores the results of a survey especially developed to document the ease of acceptance of possible characteristics to implement in mobile outdoor applications enhanced with AR. This survey has been devised for a better assessment of user preferences regarding the use of AR in outdoor scenarios. Preference level has been evaluated based on indicators from models concerning various existing and important models. The paper presents the survey results about the preference level in relation the targeted questions and proposes a conceptual framework for feedback on AR technology acceptance.